ANALISIS PENDAPAT IMAM SYAFI’I DALAM KITAB AL-UMM TENTANG PENETAPAN 1 SYAWAL BERDASARKAN KESAKSIAN RUKYATUL HILAL - Sri Wahyuningsi, Sri Wahyuningsi; Musyahid, Achmad (HISABUNA: Jurnal Ilmu Falak, 2025)
The determination of 1 Syawal is a significant issue in the Islamic calendar, closely related to the observance of religious rituals among Muslims. In this context, rukyatul hilal (crescent moon sighting) has been the primary method employed since the time of the Prophet Muhammad. This study aims to analyze the opinion of Imam al-Shafi’i regarding the determination of 1 Syawal based on the testimony of rukyatul hilal, as documented in his works, particularly in Kitab al-Umm, and to explore its relevance in the modern context. This research adopts a qualitative approach with a descriptive analytical method and is conducted as a library study. The findings show that Kitab al-Umm is one of the primary legal sources in the Shafi’i school, providing a normative foundation for the determination of lunar months, particularly 1 Syawal, by prioritizing the testimony of rukyatul hilal. Imam al-Shafi’i affirms that the sighting of the moon is a valid basis for declaring a new month, even if performed by a single just person. In the modern era, his perspective remains relevant and can be harmonized with the hisab (astronomical calculation) approach through the principle of taḥqīq al-manāṭ in contemporary ijtihad, supporting transparency and accuracy without disregarding the requirements of Islamic law.The implications of this study indicate that Imam al-Shafi’i’s thought remains highly relevant in contemporary discourse, particularly in preserving the authority of rukyat as a legitimate Islamic method. Despite the increasing complexity posed by technological developments in hisab and variations in religious authority, the Shafi’i approach offers a foundational framework for constructing an integrated system for determining the beginning of lunar months—one that combines traditional and modern methods while remaining grounded in authentic Islamic legal principles.